Isolation, Identification, and Antibiotic Susceptibility Testing of Salmonella from Slaughtered Bovines and Ovines in Addis Ababa Abattoir Enterprise, Ethiopia: A Cross-Sectional Study. (29th August 2016) - Kebede, Abe; Kemal, Jelalu; Alemayehu, Haile; Habte Mariam, Solomon
Abstract : Salmonellae are ubiquitous, found in animals, humans, and the environment, a condition which facilitates transmission and cross contamination. Salmonella enterica serotypes exert huge health and economic impacts due to their virulence or carriage of antibiotic resistance traits. To address this significant issues with regard to public health, availability of adequate information on the prevalence and antibiotic resistance patterns of Salmonella, and establishment of adequate measures to control contamination and infection are needed. A cross-sectional study was conducted to assess the level of Salmonella infection in slaughtered bovines and ovines at Addis Ababa abattoir. Samples were collected randomly and processed for identification and antimicrobial susceptibility testing of Salmonella spp. From 280 animals examined, 13 (4.64%) (8 bovines and 5 ovines) were positive, with most samples (12/13, 92%) comprising Salmonella Dublin. Very high level of resistance to some antibiotics used in human medicine was detected. Most isolates were susceptible to gentamycin and amikacin. Nine (69%) of all isolates were resistant to multiple antibiotics. Serotyping revealed 12 of 13 isolates to be of the Dublin serotype with 9, 12:g, p:- antigenic formula. This study emphasizes the importance of improving the evisceration practice during slaughtering and restricting the use of antibiotics in farm animals.